Hayek 2.0: Grundlinien einer naturalistischen Theorie wirtschaftlicher Ordnungen - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2011)
– Combining different new approaches to human behavior in neuroeconomics, the cognitive sciences and institutional economics, this paper sketches the fundamentals of a naturalistic theory of economic order. In this endeavour, the argument follows the track laid down by Hayek's comprehensive thinking about institutions and the economy, but provides new and more detailed causal accounts of the central mechanisms that link institutions and neurocognitive patterns. Based on an analytical framework to substantive institutions that has been recently proposed by Aoki, I present Hayek's theory of culture in terms of modern conceptions of performativity and distributed cognition. As a result, I introduce the concept of institutionally guided behavioral patterns, which is a modern restatement of concepts such as Veblen's habits of thought. This approach is applied on the institution of money, analyzing its emergence as a cognitive novelty that activates universal neuronal embodiments of the human penchant for social exchange and reciprocity. Against this background I argue that the naturalistic approach to economic order favours a perspective on economic policy that emphasizes cultural aspects, in particular, the formation of individual identities in different societal groups that create ethical commitments. Again, this argument is based on recent insights of the brain sciences and intends to offer an alternative to the recent proposals of a Libertarian Paternalism that have also taken insights from behavioral economics and neuroeconomics as a starting point. I show that my line of thinking can be traced back to Adam Smith, as far as the conjunction of his views in the Theory of Moral Sentiment and the Wealth of Nations is concerned.
Keywords: B41; B52; D02; D87; P0; 330; Hayek; brain and mind; culture and institutions; Aoki; language; money; dual selves; identity; Adam Smith